ANALISIS PENGARUH RESONANSI MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS MEREK PADA KONSUMEN PRODUK MAKANAN INDOMIE DI KABUPATEN KARANGANYAR - Saputro, Wahyu Ragil; Murwanti, Sri (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this research is to analyze and discuss the influence of brand resonance and brand trust on brand loyalty among consumers of Indomie food products in Karanganyar Regency. This research uses primary data through explanatory research methods based on surveys using a quantitative approach. The data source in this research is a sample of respondents who are consumers of Indomie food products in Karanganyar Regency. Data analysis uses primary data taken directly from respondents through filling out questionnaires. In this research, the sample took 200 respondents. The data analysis stage was carried out using SmartPLS 4.0 by looking at the external and internal models. The results of this research are that brand resonance (X1) and brand trust (X2) have a positive and significant effect on brand loyalty (Y) among consumers of Indomie food products in Karanganyar Regency. These results can be used as a reference for the Indomie company in making policies and carrying out product innovations through an approach to consumers based on brand resonance, brand trust and brand loyalty